The XRCC2 DNA repair gene from human and mouse encodes a novel member of the recA/RAD51 family. - Cartwright, R (1998)
We recently identified a positional candidate for the XRCC2 DNA repair gene at human chromosome 7q36.1. We have now cloned the cDNA for this gene from both human and mouse and show that it is a highly conserved novel member of the recA / RAD51 recombination repair gene family. The cDNA is able to complement significantly the phenotype of a unique cell line, irs1 , which shows extreme sensitivity to DNA cross-linking agents and genetic instability. Thisphenotype is consistent with a role for the XRCC2 gene in recombination repair in somatic cells, suggesting that in addition to RAD51 , other members of this gene family have an important function in high fidelity repair processes in mammals. Despite this function, the XRCC2 gene transcript is expressed at a very low level in somatic tissue, but is elevated in mouse testis, suggesting an additional role in meiosis.